Physicochemical assessment of Dhanmondi lake water in Dhaka city, Bangladesh - Ali, Mohammed Khorshed; Jubaer, Ahmed; Zafar, Muhammad Tasneem; Talukder, Mohammad Zahirul Islam (European Journal of Chemistry, 2022)
The main objective of this study was to examine the quality of water in the large reservoir of the Dhaka city lake and to determine whether it would be economically acceptable to purify this water for later use and to make it usable. The water quality parameters investigated are pH, temperature, electrical conductivity, hardness, alkalinity, total dissolved solids, total suspended solids, chloride, sulfate, phosphate, nitrite, nitrate, biochemical oxygen demand, chemical oxygen demand, and dissolved oxygen. The study has been done targeting three specific locations on Dhanmondi Lake, where crowds are comparatively the highest. This implies that there is a significant likelihood of pollution as well. The results of our 13-month study show that the quality of Dhanmondi lake water is somewhat higher than the international standard and some is at a tolerable level determined by the Bangladesh Department of Environment.